SAT0168 Risedronate is associated with a lower incidence of gastric ulcers than alendronate: results from two comparative studies. (1st June 2001) - Marshall, JK; Provenza, JM; Thomson, AB; Hunt, RH; Bos, KJ; Blank, MA
Abstract : Background: Bisphosphonates (BPs) are effective treatments for osteoporosis, but some have been associated with GI injury. Objectives: We compared the incidence of gastric ulcers after treatment with risedronate (RIS), a pyridinyl BP, and alendronate (ALN), a primary amino BP, in 2 similar endoscopic studies. Methods: In both studies, healthy postmenopausal women were randomised to receive RIS 5 mg or ALN 10 mg daily for 14 days. Subjects received ALN as original round tablets in Study 1 and as wax-polished oval tablets in Study 2. In Study 2, subjects were stratified by Helicobacter pylori (HP) status before randomization. Evaluator-blind assessment of the esophageal, gastric, and duodenal mucosa was performed at baseline and on Days 8 and 15 of each study. Results: In both studies, the overall incidence of gastric ulcers >3 mm was significantly lower in the RIS group than in the ALN (Table 1 ). Mean gastric erosion scores were significantly lower in the RIS group than in the ALN group at Day 8 and 15 (p < 0.001) in both studies. Mean esophageal and duodenal endoscopy scores were similar in the 2 groups at Days 8 and 15. Esophageal ulcers were noted in none of the evaluable subjects in the RIS group and in 3 in the ALN group in Study 1, and in 1 evaluable subject in the RIS group and 2 in the ALN group in Study 2. Duodenal ulcers were noted in 2 evaluable subjects in the RIS group and 1 in the ALN group in Study 1 and in none of the evaluable subjects in Study 2. In Study 2, HP infection did not increase the incidence of BP-related GI injury. Conclusion: In 2 large, comparative studies in which RIS and ALN were given at doses for the treatment of osteoporosis, the incidence of gastric ulcers was significantly lower among RIS-treated subjects than among ALN-treated subjects. Results were consistent in the 2 studies despite the difference in the shape and polish of the ALN tablets used. These findings support the hypothesis that BPs differ in their potential to produce upper GI mucosal damage.